PENENTUAN LOKASI TITIK BOR UNTUK MENDAPATKAN SUMBER AIR BERSIH DESA BANDAR RAHMAT KECAMATAN TANJUNG TIRAM KABUPATEN BATU BARA - Marwan Lubis; Luthfi Parinduri; Abdul Haris Nasution; Darlina Tanjung (Jurnal Pengabdian Mitra Masyarakat, 2022)
Availability of safe access to drinking water is one aspect of the slums of Bandar Rahmat Village. To build a good clean water well, reference data or information is needed regarding the investigation of groundwater potential around Bandar Rahmat Village, Tanjung Tiram Batubara District. This activity conducts geoelectrical testing using the resistivity method to be able to determine the value of rock resistivity which will later be used as a determination of the depth of shallow aquifers and deep aquifers. With the data obtained at each sounding point and correlated with other sounding points so that an aquifer pattern will be formed in the area. This method is used to investigate the subsurface layer based on the level of rock resistivity with groundwater (aquifer) that occupies voids in the geological layer (soil). The vertical geoelectric survey (sounding) is intended to estimate the thickness of the layer containing groundwater. The results of this survey will recommend the right drill point that can be drilled to penetrate the estimated depth so that abundant groundwater will be obtained. The next step is to make a well at the drill point for the people of Bandar Rahmat Village to use for their daily needs.